Use of natural nanobiotechnological input in a pharmaceutical formulation (Research, Society and Development, 2020)
The use of naturally occurring nanobiotechnological inputs is essential for human health and the environment. This research is of fundamental importance, given consumers' current awareness of using more natural, sustainable and healthy pharmaceutical ingredients. Thus, there has been a growing demand for more biocompatible pharmaceutical formulations with the body, which should have on their labels no aggression to nature (environment) and no use of animal testing (USP-2018). Thus, consumers want to direct the benefits that come from nature, among other means of knowledge, to their families. They are seeking to associate the cost of the finished cosmetic product with the benefit it brings to the health of the human body. In this research the continuation of studies of scientists Araújo, Giudici and Sousa, in 2019 a, b and c, which used this patented nanobiotechnological input (USP-2018), was used in the natural formulation of liquid soap.